2018
DOI: 10.1111/1755-0998.12770
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in second‐generation DNA metabarcoding results exposed with accessible and repeatable workflows

Abstract: Different second-generation sequencing technologies may have taxon-specific biases when DNA metabarcoding prey in predator faeces. Our major objective was to examine differences in prey recovery from bat guano across two different sequencing workflows using the same faecal DNA extracts. We compared results between the Ion Torrent PGM and the Illumina MiSeq with similar library preparations and the same analysis pipeline. We focus on repeatability and provide an R Notebook in an effort towards transparency for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 73 publications
0
34
0
Order By: Relevance
“…At its heart, metabarcoding is a PCR-based targeted approach in which only taxonomically informative DNA markers (i.e., barcodes) are targeted for PCR amplification and sequencing (Taberlet, Coissac, Pompanon, Brochmann, & Willerslev, 2012). While previously based on cloning and Sanger sequencing of individual bacterial colonies (Alberdi, Garin, Aizpurua, & Aihartza, 2012), today PCR products are deepsequenced on high-throughput sequencing platforms such as the lllumina MiSeq or the IonTorrent PGM (Divoll, Brown, Kinne, McCracken, & O'Keefe, 2018). Thanks to unique short nucleotide sequences appended to the 5' end of metabarcoding primers (usually called "tags" or "MIDs"; Binladen et al (2007) and/or indices to separate sequencing libraries (Murray, Coghlan, & Bunce, 2015), or both , each resulting sequence can be linked to the corresponding PCR replicate and sample.…”
Section: Box 1 Metabarcoding and Shotgun Sequencing For Dietary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At its heart, metabarcoding is a PCR-based targeted approach in which only taxonomically informative DNA markers (i.e., barcodes) are targeted for PCR amplification and sequencing (Taberlet, Coissac, Pompanon, Brochmann, & Willerslev, 2012). While previously based on cloning and Sanger sequencing of individual bacterial colonies (Alberdi, Garin, Aizpurua, & Aihartza, 2012), today PCR products are deepsequenced on high-throughput sequencing platforms such as the lllumina MiSeq or the IonTorrent PGM (Divoll, Brown, Kinne, McCracken, & O'Keefe, 2018). Thanks to unique short nucleotide sequences appended to the 5' end of metabarcoding primers (usually called "tags" or "MIDs"; Binladen et al (2007) and/or indices to separate sequencing libraries (Murray, Coghlan, & Bunce, 2015), or both , each resulting sequence can be linked to the corresponding PCR replicate and sample.…”
Section: Box 1 Metabarcoding and Shotgun Sequencing For Dietary Analysismentioning
confidence: 99%
“…). For example, one recent study on bat diet reported that only 35% of OTUs were shared amongst results when performing workflows for metabarcoding and sequencing of the same DNA extracts on different sequencing platforms(Divoll et al, 2018). Others reported differences between repeated sequencing runs of microbiome libraries on the same sequencing platform(Chase et al, 2016).Hence, if multiple sequencing runs are required, it is advisable to split samples so that fractions of all samples are sequenced in all runs, or at least avoid sequencing all samples from contrasting groups in different sequencing runs to avoid artificially inflating differences between groups.…”
mentioning
confidence: 99%
“…In addition, detection of whole communities as opposed to fewer taxa will require a greater sequencing depth (Porter and Hajibabaei, 2018b). Similar to environmental sample type, the sequencing process of DNA-based biomonitoring is often referred to as "NGS, " "High-throughput sequencing (HTS), " and "Second-generation sequencing (2GS)" (Dickie et al, 2018;Divoll et al, 2018;Zinger et al, 2019); this varying use of terminology again adds another level of inconsistency to DNAbased biomonitoring. Referring to a consistent term for this sequencing technique, similar to the ontology discussed for sample terminology, would be beneficial.…”
Section: First Termmentioning
confidence: 99%
“…Illumina sequencers generate more reads (20 million–10 billion/run) with lower error rates than Ion Torrent platforms, but the latter instruments can deliver longer reads and can generate results more rapidly (Mardis et al, ). It is unclear how severely the choice of HTS platform affects species recovery as their performance has rarely been compared in eukaryotes (Divolli, Brown, Kinne, McCracken, & O’Keefe, ). However, work on microbial communities found general agreement between platforms although reads from Ion Torrent platforms were lower quality and more length variable than those from Illumina (Salipante et al, ; Tessler et al, ).…”
Section: Introductionmentioning
confidence: 99%